DISPARITAS PENJATUHAN PIDANA TERHADAP TINDAK PIDANA PEMALSUAN SURAT - Danang Sucahyo, Purwoto, Sularto*) (Diponegoro Law Journal, 2013)
Disparity criminal is a criminal sanction is not equal to the crime or the same or similar crimes against the dangerous nature of the base can be compared without a clear justification. Factors causing criminal disparity can be derived from the law itself and also sourced from the judges themselves, both internally and externally. The criminal disparity can be minimized through two approaches, approaches to reduce disparities (which may include: the creation of guidelines by the inviter-administration of criminal law, enhancing the role of the appellate courts, the establishment of such institutions 'Sentencing Council' and the training of judges in sentencing issues) and approach to minimize the negative effect of disparity (in the form of increased role within the framework of indeterminate sentence, criminal adjustment).            Writing about the law of criminal sanctions disparity in criminal forgery using empirical juridical approach to data collection tools interviews and literature study. Interviews were conducted with free guided method. The collected data will be analyzed qualitatively understand everything that is studied, then the data associated with each other and analyzed with the existing regulations with the method of interpretation. In this qualitative analysis will be concluded by using deductive thinking, which is specific to the conclusion that the statements of generally accepted. The deductive method will produce descriptive data analysis.            Legal writing can be seen that the disparity in the criminal verdict possible forgery for the disparity is not flashy. It means that the judge can satisfy the justice of the verdict for the defendant and the community because each case has different characteristics from each other. Therefore, the judge in his ruling should not be concerned with objective elements of the perpetrator. Judges must look from the subjective factor of the case itself, as well as of other supporting factors. In addition, for the judge's decision to satisfy the justice of the necessary co-operation between law enforcement agencies including the police, prosecutor, judge advocates, and community correctional facilities.